Impact of Ground Nut Shell Ash on Cobalt-Chromium metal matrix composites synthesized using Powder metallurgy process. Issue 1 (July 2021) - Raghav, G R; Suraj, R; Janardhanan, Sheeja; Chandran, Vidya; Nagarajan, K J; Asok, Nikhil
Abstract: Co-based composites are extensively utilized in the field of prosthesis and dental implants. Hybrid composites made using Powder metallurgy process, Co-10Cr-GNSA were studied. The surface morphology of the hybrid composites were studied using Scanning Electron Microscope. The elemental analysis was carried out using X-Ray Diffraction technique. The hybrid composites were analyzed for its various mechanical properties like microhardness, compressive strength, and density. Value of micro hardness of the composite materials showed slight improvement with addition of GNSA reinforcement. The value of density of the hybrid composites was found to be decreasing linearly with the addition of GNSA. Compressive strength of the materials showed a reasonable increment. Wear analysis to study the tribological characterization of the hybrid composites were done with the help of a pin on disc wear testing machine. The wear and COF studies show that with a rise in GNSA content, wear resistance increases because of the presence of oxides of GNSA particles. From the worn out surfaces of the hybrid composite it is concluded that the deformation of the composites takes places initially due to abrasive wear followed by plastic deformation. An electrochemical workstation was used to understand the corrosion characteristics of the hybrid composites in the presence of 3% NaClelectrolyticsolution.Co-5Cr-5GNSA hybrid composites exhibit better electrochemical corrosion resistance compared to other specimens.